Accuracy of clinical examination and magnetic resonance imaging in arthroscopic knee surgery - Wutphiriya-angkul, MD, Somboon (Journal of Southeast Asian Orthopaedics, 2022)
Background and objectives: Diagnosis in knee injuries consist of clinical examinations and magnetic resonance imaging (MRI). The accuracy of these methods are varied. We performed a retrospective study to seek the accuracy of clinical examination and magnetic resonance imaging in arthroscopic knee surgery. Materials and methods: A total of 44 patients were selected for review. Data including sensitivity, specificity, accuracy, positive predictive value, and negative predictive value were calculated. Results: Arthroscopic examination should be kept as standard. The Lachman test is the most sensitive test to determine ACL tears, showing a sensitivity of 83% (95% confidence interval 0.64-0.99). The pivot shift test is the most specific test, showing a specificity of 85% (95% confidence interval 0.68-0.96). The McMurray test is the most sensitive test to determine meniscus tears, showing a sensitivity of 87% (95% confidence interval 0.76-0.96). The Apley test is a more specific test, showing a specificity of 86% (95% confidence interval 0.72-0.96). MRI of ACL showed a sensitivity of 96% (95% confidence interval 0.86-0.99). MRI of medial meniscus is a more sensitive test to determine meniscus tears, showing a sensitivity of 97% (95% confidence interval 0.88-0.99), MRI of lateral meniscus showed a sensitivity of 93% (95% confidence interval 0.84-0.99). Conclusion: The clinical examination is an important and accurate diagnostic modality for the evaluation of knee injury. MRI is a more accurate diagnostic modality than clinical examination. It should be used when there is an uncertain indication for surgery.